Utilization and Development Strategy of PLG Peat Land in Central Kalimantan - DIDI ARDI SURIADIKARTA (Indonesian Center for Agriculture Land Resource Development, 2008)
Swampy lands in Indonesia are covering a very large area which are distributed in three main islands i.e. Sumatra, Kalimantan, and Papua. The total areas of swampy lands are 33.4 millions ha, that consist of tidal land areas covering 20 millions ha more or less, and about 13.4 millions ha of non tidal lands. To develop swampy land area need good planning with proper technological application, especially in soil and water management. The objective of opening swampy land areas is to overcome the decreasing of rice productivity of rice field in Java. This is due to landuse conversion to another function, such as office building, highway, roads, and manufactures. PLG areas consist of four blocks, namely Block A, B, C, and D which covers 268,000 ha, 156,000 ha, 570,000 ha, and 138,000 ha, respectivelly. The strategy for developing these areas are: 1) To make master plan of PLG areas, 2) The peat land that has a thickness more than 3 meters utilized for conservation areas, 3) The peat land with less than 3meters thickness will be utilized for developing agriculture, fishery and forestry, 4) Protection areas for developing biodivercity. If those strategies are being conducted, thus the rehabilitation and revitalization of this area will be easily executed. According to the research result conducted by Agency of Agricultural Research and Development during the period of 1997-2000 in these areas, it is indicated that the soils are very potential for food crops, horticultures, and fruits. The limiting factors of these areas are pest, diseases, and flooding at the peak of rainy season. These areas are very potential for agribusiness such as food crops, vegetable crops, fruits, and estate crops, if macro water management network can be functioned normally and limiting factors can be controlled.